2010
DOI: 10.1186/1757-1626-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac tamponade and successful pericardiocentesis in an extremely low birth weight neonate with percutaneously inserted central venous line: a case report

Abstract: BackgroundPericardial effusion and cardiac tamponade are rare but life-threatening complications of percutaneosuly inserted central line (PICL) use in extremely low birth weight (ELBW) neonates, with an incidence reported between 0.07% and 2% of PICLs placement. Timely diagnosis and pericardiocentesis has been proven to be life-saving.Case presentationThe patient was a 620 g birth weight neonate who presented with sudden cardiac instability 18 days after the insertion of a PICL and in spite of a presumed satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…15 In children, as in adults, we recommend that positioning the CVC tip above the carina means it is likely to be in the superior vena cava and therefore outside the pericardial sac (LOE 3, RG 0, strong recommendation for, strong consensus) R 10. 16 The catheter tip of a femoral catheter should lie above the renal veins (first lumbar vertebra) (GPP, strong recommendation for, strong consensus) material [53,54] (LoE 3). Weil et al reported a pericardial effusion causing pericardial tamponade due to CVC in 1.3% of all children who experienced tamponade and all of these children were newborns [55] (LoE 3).…”
Section: Positioning Of the Catheter Tipmentioning
confidence: 99%
“…15 In children, as in adults, we recommend that positioning the CVC tip above the carina means it is likely to be in the superior vena cava and therefore outside the pericardial sac (LOE 3, RG 0, strong recommendation for, strong consensus) R 10. 16 The catheter tip of a femoral catheter should lie above the renal veins (first lumbar vertebra) (GPP, strong recommendation for, strong consensus) material [53,54] (LoE 3). Weil et al reported a pericardial effusion causing pericardial tamponade due to CVC in 1.3% of all children who experienced tamponade and all of these children were newborns [55] (LoE 3).…”
Section: Positioning Of the Catheter Tipmentioning
confidence: 99%
“…In the intensive care setting, predisposing factors for PCE are hydrops, complication of central venous catheters or cardiac operations, sepsis, thyroid hormone dysfunction and tumors (3). It can be complicated with cardiac tamponade and presented as sudden cardiac collapse or unexplained cardiorespiratory instability (bradycardia, cyanosis and metabolic acidosis) that can be confused with the symptoms of sepsis (4,5). It is diagnosed with echocardiography if considered.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the rate of fluid accumulation, pericardial tamponade manifests on a continuum from elevated venous pressure without hemodynamic changes or symptoms to cardiogenic shock and death. Fatal cardiac tamponade has been described with acute effusions of as little as 2 mL in neonates 2 and 200 mL in adults, 3 although relative hemodynamic stability can be maintained with slowly-accumulated effusions of 10 times that volume in chronic disease. 3,4 The etiology of cardiac tamponade can be organized into traumatic (blunt or penetrating) and nontraumatic causes.…”
Section: Discussionmentioning
confidence: 99%